ASPEK HUKUM TANGGUNG JAWAB NEGARA TERHADAP PERLINDUNGAN ANAK TERLANTAR DITINJAU DARI PASAL 34 AYAT 1 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Anna Syahra; Mulati . (Jurnal Hukum Adigama, 2018)
Children is a gift from god that we need to keep, protect and take care of, as good as we can. It was the philosophy which created the idea of the Nation has responsibilities to take care of the waifs. Constitution of Indonesia has been adopted the idea then mandating our nation to take care the destitude and the waifs. The idea itself has been created in the form of regulation in Indonesia, therefore, Indonesia that represented by the government liable to protect and take care of the waifs. In the other hand, the waifs in Indonesia still shown the big number of quantity, it means, there is a problem in the system of handling the waifs that used by the government to fulfill the rights of the waifs. As a regulation mandates the government to fulfill the rights of the waifs and also protect and take care of the waifs, the government faced the obstacle. The obstacle has raised from many factor, such as regulation, the integration between institution related to the waifs, the funds, and the involvement of the public are not used by the government. The obstacle itself cause the government can not perform the obligation to fulfill and protect the rights of the waifs effectively and perfectly.